Penerapan metode full costing dalam penentuan harga pokok produksi pada Gav’s Furniture - Rakinaung, Alvionita Aprilia; Gerungai, Natalia Y.T.; Suwetja, I Gede (Manajemen Bisnis dan Keuangan Korporat, 2025)
Determining the cost of production is very important for a business because it is the basis for determining future business profits. The Full Costing method is a method of cost of production (HPP) that considers all production costs, both direct and indirect costs. This study aims to determine whether the application of the full costing method can help Gav's Furniture determine the cost of production accurately. The type of research used is qualitative with a descriptive approach. The types of data used are primary and secondary data with data collection, namely interviews and documentation. The results of the study indicate that by using the full costing method, the cost of production of Gav's Furniture is higher because this method calculates all fixed and variable costs, so that the cost of production is accurate because each cost is included in the components of the cost of production, namely raw materials, labor, and factory overhead. The implication of this research is that the use of the full costing method can assist small and medium-sized enterprises (SMEs) in making more precise pricing decisions and improving profit planning by ensuring that all relevant production costs are properly allocated and considered.